Innate immune cells in the pathogenesis of inflammatory bowel disease - from microbial metabolites to immune modulation - Mousa, Rabia S.; Invernizzi, Pietro; Mousa, Hani S. (Frontiers in Gastroenterology, 2024)
Inflammatory Bowel Disease (IBD) is a term used to describe a group of disorders characterized by chronic inflammation of the gastrointestinal tract, with Crohn’s Disease (CD) and Ulcerative Colitis (UC) being the most common. While still not fully understood, pathogenesis is believed to be multifactorial – the result of an interplay between genetic susceptibility, immune dysregulation and environmental factors that all lead to chronic inflammation and tissue remodeling. Innate immune cells, which orchestrate the initial defense mechanisms and modulate the subsequent immune response, play a central role in disease initiation and progression. This review examines the complex involvement of innate immune cells in IBD, emphasizing their interactions with environmental factors and the gut microbiome. We highlight the importance of microbial dysbiosis and impaired intestinal barrier function in disease pathogenesis, and the role that innate immune cells play not only as first responders, but also as key players in maintaining intestinal barrier integrity and gut microbiome. This review provides a comprehensive summary of the role that innate immune cells play in IBD pathogenesis with emphasis on the increasingly recognized role of the gut microbiome. A better understanding of innate immune cell mechanisms and of microbiome-immune interactions is key for the development of novel targeted therapies.